The semantic field of the word ‘snow’ in Yakut dialects - Nikolaev Егор (Turkic Studies Journal, 2024)
The article presents an analysis of the semantic features of the word ‘snow’ in Yakut dialects. The semantic field of khaar ‘snow’ has been defined through component and semantic analyses. The interpretation of ‘khaar’ in various dialects is based on a comparison of the physical characteristics of snow. The study has shown that the words denoting snow reveal the related meanings of snow such as ‘lush,’ ‘loose,’ and ‘fluffy.’ The analysis has demonstrated that certain words considered in this article possess a connotative feature of peripheral meanings. The semantic field of ‘khaar’ constitutes the semantic space of Yakut words denoting ‘snow’, which is distinguished by a number of features. Firstly, the term is prevalent in different subdialects. Secondly, the stem word khaar unites some features describing different types of snow. Thirdly, the usage of the dialect of ‘khaar’ in one or several dialect zones has resulted in the expansion of the subdialect areas (Kolyma, Vilyui). The semantic space of ‘khaar’ represents the linguistic worldview as a result of long-term observations of the surrounding environment. The significance of the study lies in the linguistic description of Yakut everyday life.